2008
DOI: 10.1123/jpah.5.s1.s153
|View full text |Cite
|
Sign up to set email alerts
|

Pedometer-Determined Physical Activity, BMI, and Waist Girth in 7- to 16-Year-Old Children and Adolescents

Abstract: Background: Different approaches to measuring physical activity and fatness in youth have resulted in studies reporting relationships ranging from very strong to nonexistent. Methods: The sample comprised 787 boys and 752 girls between the ages of 7 and 16 years. Pedometer-determined physical activity, height, weight, and waist girth measures were taken. Results: Significant differences were found in activity level between body mass index-determined weight categories for the girls (F 1,742 = 9.07, P = .003) bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
17
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 50 publications
(59 reference statements)
9
17
0
1
Order By: Relevance
“…Furthermore, physical activity outcomes were consistent with previous findings that the boys in the sample took more steps per day compared to girls [9,[15][16][17]. Boys had assessed and more engaged in neighborhood physical activity while girls participated in more passive activities like socializing, instead involved directly in physical activity [18].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Furthermore, physical activity outcomes were consistent with previous findings that the boys in the sample took more steps per day compared to girls [9,[15][16][17]. Boys had assessed and more engaged in neighborhood physical activity while girls participated in more passive activities like socializing, instead involved directly in physical activity [18].…”
Section: Discussionsupporting
confidence: 87%
“…The averages detailed in the current study are most consistent with those reported in a large nationally representative sample of Malaysian children aged 7 to 12 years [9]. However, this sample of obese children was clearly more inactive when compared with other European studies, such as those from Ireland [15] and Greece [16] that have reported approximately 10000 to 13000 daily steps and was also less active than Australian obese children [17].…”
Section: Discussionsupporting
confidence: 86%
“…n Includes 48 studies (Ekelund et al 2004Andersen et al 2006;Duncan et al 2006Duncan et al , 2008Lohman et al 2006Lohman et al , 2008Ness et al 2007;Ortega et al 2007Ortega et al , 2010Stevens et al 2007;Hurtig-Wennlof et al 2007;Hands and Parker 2008;Hands et al 2009;Mark and Janssen 2009;Riddoch et al 2009;Steele et al 2009;Treuth et al 2009;Ferrar and Olds 2010;Martinez-Gomez et al 2010b;Owen et al 2010;Dollman et al 2010;Kelly et al 2010;Belcher et al 2010;Peart et al 2011;Holman et al 2011;…”
Section: S203 Published By Nrc Research Pressmentioning
confidence: 99%
“…Many studies have proven the hypothesis that lower PAL causes overweight and leads to an increase in the parameters of body composition and vice versa [26, 31-33, 37, 41, 42, 44-47], while one study did not record significant differences in the body composition in relation to PAL [30]. In two studies [34,36], active boys had higher bMI values, but in all parameters of functional abilities they were superior compared with the inactive group.…”
Section: Resultsmentioning
confidence: 98%
“…To assess the level and intensity of PA, researchers used different equipment, like accelerometers [29,31,35,37,38] or pedometers [30], objectively measuring PAL, or less objective measures, like questionnaires [32, 38-40, 43, 45-47]. The system of calculating calorie consumption by the metabolic equivalent of task (METs), derived by questionnaires, was applied in two studies [31,32].…”
Section: Resultsmentioning
confidence: 99%